1992
DOI: 10.1104/pp.99.4.1619
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Processing of Polyphenol Oxidase in a Variegated Grapevine Mutant

Abstract: Bruce's Sport is a mutant grapevine (Vitis vinifera L.) with green and white variegated fruit derived from the Sultana variety. The white regions of tissue have decreased polyphenol oxidase (PPO) activity resulting in a reduced capacity for browning. Active PPO from Sultana grapes was purified and had an apparent molecular weight of 40,000 on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
3
42
1
Order By: Relevance
“…PPO B is the most abundant PPO mRNA in young tomato leaves (nodes 1-3); levels of this transcript subsequently decline as leaves mature (node 5 ) . The presence of PPO transcripts primarily at early developmental stages has been observed previously in tomato, potato, and grape berries (Rathjen and Robinson, 1992;Shahar et al, 1992;Hunt et al, 1993;Thygesen et al, 1995). In contrast, broad bean PPO transcripts are abundant in mature leaves (Cary et al, 1992).…”
Section: Discussionmentioning
confidence: 52%
“…PPO B is the most abundant PPO mRNA in young tomato leaves (nodes 1-3); levels of this transcript subsequently decline as leaves mature (node 5 ) . The presence of PPO transcripts primarily at early developmental stages has been observed previously in tomato, potato, and grape berries (Rathjen and Robinson, 1992;Shahar et al, 1992;Hunt et al, 1993;Thygesen et al, 1995). In contrast, broad bean PPO transcripts are abundant in mature leaves (Cary et al, 1992).…”
Section: Discussionmentioning
confidence: 52%
“…As protease inhibitors did not modify the activation rate, the activation process could not be ascribed to the existence of a proenzyme, as it has been described for insect, crustacean and Ðsh phenolases (Wang et al 1994 ; Aspan et al 1995). Rathjen and Robinson (1992) for grapevine PPO and So derha ll (1995) for carrot PPO also suggested that a ProPPO, a 60 kDa molecule, was converted into its active form (a 40 kDa PPO) by a limited proteolysis. Addition of detergent (SDS), alcohol (ethanol), fatty acid (linoleic acid) or protease (trypsin) to pear PPO crude extract enhanced the activation rate (Fig 1).…”
Section: Resultsmentioning
confidence: 91%
“…Several factors have been postulated to be involved in activation. They include : (i) a proenzyme (Rathjen and Robinson 1992 ;Aspan et al 1995 ;So derha ll 1995) ; (ii) a PPO-bound inhibitor (Sanchez-Ferrer et al 1993) ; and (iii) a conformational change (Lerner and Mayer 1975 ;Marques et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…2). Proteolytic processing of many other PPOs has been described, such as the PPO enzymes found in broad bean leaf (Vicia faba; Robinson and Dry, 1992), grape (Vitis vinifera; Rathjen and Dry, 1992), and coffee (Coffea arabica; Mazzafera and Robinson, 2000). More recently, Flurkey and Inlow (2008) analyzed T. officinale (2), T. kok-saghyz (3), H. brasiliensis (4), and F. elastica (5); all the plants listed above were harvested after wounding by drawing into 10-mL microglass capillaries.…”
Section: Discussionmentioning
confidence: 99%